Nanometer metal gel admixture as well as preparation method and application thereof

By adding prepared nanometal gel admixtures to the concrete repair materials, the problems of aging and falling off and high brittleness of existing repair materials under harsh conditions are solved, and the adaptability of toughness, bonding strength and volume change are achieved, extending the service life of repair materials.

CN119505049AInactive Publication Date: 2025-02-25UNIV OF JINAN
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411824760.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing concrete repair materials are prone to aging and falling off under harsh conditions such as freeze-thawing and seawater corrosion, high brittleness, low bonding strength, poor impact resistance, and unfit volume changes, resulting in fallout and cracking of repair materials.

Method used

By preparing nanometal gel admixtures, using raw materials such as vinyl acetate and aluminum acetate, nanometal gels are formed through polycondensation reaction and affinity addition reaction, and added to cement-based repair materials to improve its volume change adaptability and binding ability with the concrete structure.

Benefits of technology

It significantly improves the toughness and bonding strength of the repair material, enhances crack resistance, improves the adaptability of volume changes, extends the service life of the repair material, and reduces the fall-off and cracking of the repair material under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505049A_ABST
    Figure CN119505049A_ABST
Patent Text Reader

Abstract

The invention discloses a nano metal gel admixture as well as a preparation method and application thereof. The method comprises the following steps: (1) uniformly mixing vinyl acetate, alkali liquor and water, and then carrying out hydrolysis-polymerization reaction on the obtained mixture under heating and pressurizing conditions to obtain a liquid phase containing a polymer; and (2) heating the liquid phase containing the polymer, preserving heat, adding aluminum acetate powder under a stirring condition, and carrying out affinity addition reaction to obtain a liquid phase containing the nano-metal polymer. And (3) adding a dispersing agent and a stabilizing agent into alkaline water, uniformly mixing, then adding the liquid phase containing the nano-metal polymer, and carrying out high-speed shearing treatment to obtain the nano-metal gel. Through chemical bonding and mechanical interlocking effects of the prepared special metal gel and the cement hydration product, the volume change adaptation rate and the bonding capacity between the repairing material and a concrete structure are effectively improved, and the service life of the repairing material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete structure repair materials, and in particular to a nano metal gel admixture and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Cement concrete is the most widely used and largest amount of engineering construction material in my country. It plays an irreplaceable role in urban construction, road paving and marine development. However, in the long-term service process, due to freeze-thaw cycles, seawater scouring, vehicle loads and other effects, cement concrete facilities will produce many minor diseases, such as honeycomb pockmarks on roads, micro cracks in walls and seawater corrosion leading to damage to cement concrete structures. If the buildings with these minor diseases are not repaired in time, these infrastructures will suffer from a series of more serious diseases such as large-scale damage and falling off, which will affect the normal use of the buildings and cause a series of safety problems. Therefore, it is necessary to repair the infrastructure with minor diseases to reduce the occurrence of diseases and further extend the service life of the buildings.

[0004] At present, the repair materials for concrete buildings mainly include organic repair materials and inorganic repair materials. Among them, although organic repair materials have high bonding strength, they are easily affected by factors such as freeze-thaw damage and ultraviolet radiation during use, resulting in aging and falling off, that is, poor durability, and the price of organic repair materials is generally expensive, and they are not suitable for large-area repairs. Inorganic repair materials not only have the problems of large brittleness, low bonding strength, poor impact resistance, and easy cracking, but also because the volume change rate between them and the concrete matrix is ​​quite different, the new and old interfaces of the repaired parts will be inconsistent due to volume changes under changes in ambient temperature, resulting in shrinkage, cracking, and debonding of inorganic repair materials. In addition, there are also organic-inorganic combined repair materials, such as polymer cement-based repair materials, but because the polymer will be adsorbed on the surface of cement particles and the water in the repair material to form a membrane to wrap the cement particles, it will hinder the contact between cement particles and water, which will lead to insufficient hydration of cement components and reduce the strength of the repair material. Summary of the invention

[0005] In view of this, the present invention provides a nano-metal gel admixture and its preparation method and application, which effectively improves the volume change adaptation rate and bonding ability between the repair material and the concrete structure through the chemical combination and mechanical interlocking effect of the prepared special metal gel and the cement hydration product, and improves the service life of the repair material. Specifically, the technical solution of the present invention is as follows.

[0006] First, the present invention provides a cement-based repair material nano-metal gel admixture, whose chemical structure is shown in formula (1):

[0007]

[0008] In the above formula (1), n=100 to 5000.

[0009] Secondly, the present invention provides a method for preparing a nano-metal gel admixture for cement-based repair materials, comprising the following steps:

[0010] (1) Vinyl acetate, alkali solution and water are mixed and then the resulting mixture is subjected to a hydrolysis-polymerization reaction under heating and pressure conditions to obtain a liquid phase containing a polymer.

[0011] (2) The liquid phase containing the polymer is heated and then kept warm, and then aluminum acetate powder is added under stirring conditions to carry out affinity addition reaction, and after completion, a liquid phase containing nano-metal polymer is obtained.

[0012] (3) adding a dispersant and a stabilizer into alkaline water and mixing them evenly, then adding the liquid phase containing the nano-metal polymer and subjecting it to high-speed shearing treatment, and obtaining the nano-metal gel after completion.

[0013] Furthermore, in step (1), the ratio of vinyl acetate, alkali solution and water is 15-28 parts by weight: 10-13 parts by weight: 3-10 parts by weight. Optionally, the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution and the like.

[0014] Furthermore, in step (1), the heating temperature is 150-180°C, the pressurized pressure is 0.5-1.0 MPa, and the reaction time is 4-8 hours. In this process, the acetic acid groups in the vinyl acetate react with the alkali solution (for example, sodium hydroxide) to undergo a hydrolysis reaction, and then undergo a polycondensation reaction under high temperature and pressure to form a polymer, as shown in formula (2).

[0015]

[0016] Furthermore, in step (2), the ratio of the liquid colloid containing the polymer to the aluminum acetate powder is 41 to 61 parts by weight: 8 to 10 parts by weight.

[0017] In the step (2), the heating temperature is 40-90° C. and the reaction time is 2-4 hours. In this process, the carbonyl group of the polymer and the aluminum acetate undergo an affinity addition reaction and are combined through coordination to form the nano-metal polymer, as shown in formula (3).

[0018]

[0019] Furthermore, in step (3), the pH of the alkaline water is 8 to 11. Optionally, the alkaline water is prepared by mixing an alkali solution with water. The alkali solution includes at least one of a potassium hydroxide solution, a sodium hydroxide solution, a saturated calcium hydroxide solution, and the like.

[0020] Furthermore, in step (3), the ratio of the dispersant, the stabilizer, the alkaline water, and the liquid phase containing the nano-metal polymer is 0.2-0.6 parts by weight: 1-3 parts by weight: 40-55 parts by weight: 46-66 parts by weight.

[0021] Furthermore, in step (3), the dispersant includes at least one of sodium dodecylbenzene sulfonate, methyl cellulose ether, polyacrylamide, etc.

[0022] Furthermore, in step (3), the stabilizer includes at least one of nano-silicon dioxide, sodium silicate, etc.

[0023] Furthermore, in step (3), the rate of the high-speed shearing treatment is 1500 to 5000 r / min, and the time is 15 to 30 min.

[0024] Finally, the present invention provides the application of the nano-metal gel admixture in cement-based repair materials. The raw material composition of the repair material includes component A and component B, wherein: component A includes 38 to 45 parts by weight of silicate cement, 45 to 60 parts by weight of fine aggregate, 0.1 to 0.25 parts by weight of water reducer, 0.3 to 0.6 parts by weight of early strength agent, 5 to 8 parts by weight of ultrafine powder, and 0.1 to 0.3 parts by weight of fiber. Component B includes 20 to 35 parts by weight of the nano-metal gel of the present invention and 50 to 70 parts by weight of water. When in use, mix the A and B components evenly, then apply them to the part to be repaired, and wait for solidification and hardening.

[0025] Furthermore, the fine aggregate includes at least one of quartz sand, river sand, machine-made sand, etc.

[0026] Furthermore, the water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, and the like.

[0027] Furthermore, the early strength agent includes at least one of sodium sulfate, lithium carbonate, sodium silicate and the like.

[0028] Further, the ultrafine powder includes at least one of ultrafine fly ash, ultrafine mineral powder, ultrafine composite mineral admixture, etc. Optionally, the ultrafine powder has a fineness of 500-600 mesh.

[0029] Furthermore, the early strength agent includes at least one of sodium sulfate, lithium carbonate, triethanolamine, etc.

[0030] Further, the fiber includes at least one of carbon fiber, polypropylene fiber, polyvinyl alcohol fiber, polyacrylonitrile fiber, etc. Optionally, the length of the fiber is 3 to 12 mm.

[0031] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:

[0032] The present invention uses vinyl acetate and aluminum acetate as raw materials, and prepares a nano-metal gel through condensation reaction and affinity addition reaction. Adding it to the repair material can greatly improve its toughness and bonding strength, thereby improving the crack resistance of the repair material, and better coping with the damage caused by various harsh conditions to roads, walls, marine cement concrete and other building structures. At the same time, the repair material with the nano-metal gel also has better volume deformation ability. When the concrete structure and the repair material change in volume due to the influence of ambient temperature, the repair material of the present invention has a good volume change adaptation rate with the concrete structure, which alleviates the problem of the repair material falling off and improves the service life of the repair material. The reason is:

[0033] On the one hand, the present invention introduces Al into the polymer matrix through the affinity addition reaction between the polymer and aluminum acetate. 3+ When the metal gel is mixed with cement material, the Al in the gel 3+ OH released by cement hydration - , Ca 2+ And the SO4 provided by the silicate cement and early strength agent 2- The reaction between the cement and the gel induces the formation of calcium sulfonate and aluminum hydroxide gel in situ on the surface of the gel, so that the cement and the gel are chemically connected, and the connection ability between the cement particles and the gel and the hydration products is increased. When the cement shrinks, the gel will produce a physical and chemical synergistic interlocking effect with the cement hydration products, and give full play to the high toughness of the gel when bearing force, thereby improving the fracture energy of the cement matrix and resisting the cracking of the matrix. At the same time, the good toughness of the nano-metal gel effectively improves the volume change ability of the repair material and improves the volume change adaptation rate between the repair material and the concrete structure.

[0034] On the other hand, the interface transition zone between the repair material and the concrete structure is a weak zone, which is also the main reason for the debonding and cracking of the repair material during service. 3+ In alkaline cement paste, it will provide SO4 2-The hydration product calcium hydroxide in the old concrete interface undergoes a hydration reaction to generate needle-rod-shaped calcium aluminate, which converts the weak factor calcium hydroxide into a favorable hydration product with gelling characteristics, strengthens the interface transition zone between the repair material and the concrete structure, and improves the bonding strength between the two. At the same time, the nano-metal gel can also play a nucleation effect, induce more high-stability cement hydration products to be generated in the interface transition zone, fill the pores in the interface transition zone, and improve the bonding strength between the repair material and the concrete structure. The nano-silicon dioxide in the nano-metal gel can also play a size effect, a nucleation effect, and an activity effect, so that the nano-silicon dioxide will react with calcium hydroxide to generate CSH gel. It also helps to convert the weak factor calcium hydroxide into a favorable factor with gelling characteristics. In addition, the van der Waals attraction between the needle-rod-shaped calcium aluminate and the nano-metal gel and CSH gel forms a denser and stronger interface transition zone.

[0035] Furthermore, the present invention further improves the toughness of cement repair materials by using the nano-metal gel and fiber gradient toughening method. This is because when the cement repair material is subjected to impact and load, the high-toughness nano-metal gel first deforms to offset part of the impact stress, and the bridging effect of the fiber in the cement repair material disperses the stress concentrated in the load-bearing area of ​​the cement repair material, making the repair material bear stress more evenly, increasing the toughness of the cement and reducing the cracking driving force of the cement-based repair material when subjected to stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0037] Figure 1 This is a picture of the nanometal gel sample prepared in Example 1.

[0038] Figure 2 This is the infrared test result of the nano-metal gel prepared in Example 1.

[0039] Figure 3 This is a bonding strength test diagram of Example 1.

[0040] Figure 4 This is the infrared test result of the nanometal gel prepared in Example 5. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0042] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0043] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0044] Example 1

[0045] 1. A method for preparing a cement-based repair material nano-metal gel admixture, comprising the following steps:

[0046] (1) 20 parts by weight of vinyl acetate, 11 parts by weight of sodium hydroxide, and 7 parts by weight of water were added to a reactor, and then heated to 50° C. and stirred for 10 minutes. The reactor was then heated to 160° C. and the pressure was set to 0.75 MPa for 6 hours to perform a hydrolysis-polymerization reaction. After completion, the reaction was cooled to room temperature to obtain a liquid phase containing a polymer for standby use.

[0047] (2) 47 parts by weight of the liquid phase containing the polymer is taken, heated to 45° C. and kept at a constant temperature, and then 8.5 parts by weight of aluminum acetate powder is added. After completion, the temperature is kept constant for 2 hours to perform an affinity addition reaction. After completion, a liquid phase containing a metal polymer is obtained and is set aside.

[0048] (3) 0.35 parts by weight of dispersant (sodium dodecylbenzene sulfonate) and 2 parts by weight of stabilizer (nano-silica) were added to 50 parts by weight of potassium hydroxide solution with pH=10 and magnetically stirred for 8 minutes. Then 55 parts by weight of the liquid phase of the metal-containing polymer was added and high-speed shearing was performed at a speed of 2000 r / min for 20 minutes. After completion, nano-metal gel was obtained. The physical sample and infrared test results were as follows: Figure 1 , Figure 2 shown.

[0049] 2. A method for preparing a high-toughness cement-based repair material, comprising the following steps:

[0050] (1) Weigh the following components: 40 parts by weight of 42.5 ordinary Portland cement, 52 parts by weight of quartz sand fine aggregate with a fineness between 10 and 100 meshes, 0.15 parts by weight of polycarboxylate water reducer, 0.5 parts by weight of sodium sulfate powder, 6 parts by weight of ultrafine mineral powder with a fineness of 500 meshes, and 0.2 parts of carbon fiber with a length of 3 mm. Mix the above components evenly to obtain component A.

[0051] (2) Take 28 parts by weight of the nanometal gel prepared in this example, mix it with 60 parts by weight of water and stir evenly to obtain component B.

[0052] (3) The component A and the component B are mixed and stirred evenly to obtain a cement-based repair material.

[0053] Performance test: The bonding strength (such as Figure 3 The elongation at break of the cement-based repair material was tested in accordance with GB / T16777-2008 "Test Methods for Building Waterproof Coatings". The cracking index of the cement-based repair material was tested in accordance with GBT 29417-2012 "Test Methods for Drying Shrinkage Cracking Performance of Cement Mortar and Concrete". The test results are shown in the following table.

[0054] Bond Strength Flexural strength Elongation at break Cracking index 2.77MPa 11.94MPa 8.62% 36.51%

[0055] Example 2

[0056] 1. A method for preparing a cement-based repair material nano-metal gel admixture, comprising the following steps:

[0057] (1) 15 parts by weight of vinyl acetate, 10 parts by weight of sodium hydroxide, and 3 parts by weight of water were added to a reactor, and then heated to 50° C. and stirred for 8 minutes. The reactor was then heated to 150° C. and the pressure was set to 1.0 MPa for 4 hours to perform a hydrolysis-polymerization reaction. After completion, the reaction was cooled to room temperature to obtain a liquid phase containing a polymer for standby use.

[0058] (2) Take 41 parts by weight of the liquid phase containing the polymer, heat it to 40° C. and keep it constant, then add 8 parts by weight of aluminum acetate powder. After completion, continue to keep the temperature at this temperature for 3 hours to carry out affinity addition reaction. After completion, a liquid phase containing a metal polymer is obtained and set aside.

[0059] (3) 0.2 parts by weight of a dispersant (methyl cellulose ether) and 1 part by weight of a stabilizer (nano-silica) were added to 40 parts by weight of a sodium hydroxide solution with a pH of 11, and the mixture was magnetically stirred for 8 minutes. Then, 46 parts by weight of the liquid phase of the metal-containing polymer was added, and the mixture was sheared at a speed of 1500 r / min for 30 minutes to obtain a nano-metal gel.

[0060] 2. A method for preparing a high-toughness cement-based repair material, comprising the following steps:

[0061] (1) Weigh the following components: 38 parts by weight of 42.5 ordinary Portland cement, 45 parts by weight of river sand fine aggregate with a fineness between 10 and 100 meshes, 0.1 parts by weight of polycarboxylate water reducer, 0.3 parts by weight of sodium sulfate powder, 5 parts by weight of ultrafine fly ash with a fineness of 600 meshes, and 0.1 parts of polypropylene fiber with a length of 10 mm. Mix the above components evenly to obtain component A.

[0062] (2) Take 20 parts by weight of the nanometal gel prepared in this example, mix it with 50 parts by weight of water and stir evenly to obtain component B.

[0063] (3) The component A and the component B are mixed and stirred evenly to obtain a cement-based repair material.

[0064] Performance test: The bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The test results are shown in the following table.

[0065] Bond Strength Flexural strength Elongation at break Cracking index 2.38MPa 12.76MPa 8.94% 32.73%

[0066] Example 3

[0067] 1. A method for preparing a cement-based repair material nano-metal gel admixture, comprising the following steps:

[0068] (1) 28 parts by weight of vinyl acetate, 13 parts by weight of sodium hydroxide, and 10 parts by weight of water were added to a reactor, and then heated to 50° C. and stirred for 10 minutes. The reactor was then heated to 180° C. and the pressure was set to 0.5 MPa for 8 hours to perform a hydrolysis-polymerization reaction. After completion, the reaction was cooled to room temperature to obtain a liquid phase containing a polymer for standby use.

[0069] (2) 61 parts by weight of the liquid phase containing the polymer are taken, heated to 90° C. and kept at a constant temperature, and then 10 parts by weight of aluminum acetate powder are added. After completion, the temperature is kept constant for 4 hours to carry out an affinity addition reaction. After completion, a liquid phase containing a metal polymer is obtained and is set aside.

[0070] (3) 0.6 parts by weight of a dispersant (polyacrylamide) and 3 parts by weight of a stabilizer (sodium silicate) were added to 55 parts by weight of a potassium hydroxide solution with a pH value of 8, and the mixture was magnetically stirred for 12 minutes. Then, 55 parts by weight of a liquid phase of the metal-containing polymer was added, and the mixture was sheared at a speed of 5000 r / min for 15 minutes to obtain a nanometal gel.

[0071] 2. A method for preparing a high-toughness cement-based repair material, comprising the following steps:

[0072] (1) Weigh the following components: 45 parts by weight of 42.5 ordinary Portland cement, 60 parts by weight of quartz sand fine aggregate with a fineness between 10 and 100 meshes, 0.25 parts by weight of sodium lignin sulfonate water reducer, 0.6 parts by weight of lithium carbonate powder, 8 parts by weight of ultrafine mineral powder with a fineness of 550 meshes, and 0.3 parts of polyvinyl alcohol fiber with a length of 12 mm. Mix the above components evenly to obtain component A.

[0073] (2) Take 35 parts by weight of the nanometal gel prepared in this example, mix it with 70 parts by weight of water and stir evenly to obtain component B.

[0074] (3) The component A and the component B are mixed and stirred evenly to obtain a cement-based repair material.

[0075] Performance test: The bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The test results are shown in the following table.

[0076] Bond Strength Flexural strength Elongation at break Cracking index 3.22MPa 13.60MPa 9.48% 29.82%

[0077] Example 4

[0078] A method for preparing a cement-based repair material comprises the following steps:

[0079] (1) Weigh the following components: 40 parts by weight of 42.5 ordinary Portland cement, 52 parts by weight of quartz sand fine aggregate with a fineness between 10 and 100 meshes, 0.15 parts by weight of polycarboxylate water reducer, 0.5 parts by weight of sodium sulfate powder, 6 parts by weight of ultrafine mineral powder with a fineness of 500 meshes, and 0.2 parts of carbon fiber with a length of 3 mm. Mix the above components evenly to obtain component A.

[0080] (2) The component A is mixed with 60 parts by weight of water and stirred evenly to obtain a cement-based repair material.

[0081] Performance test: The bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The test results are shown in the following table.

[0082] Bond Strength Flexural strength Elongation at break Cracking index 1.31MPa 9.23MPa 0.15% 71.54%

[0083] Example 5

[0084] A method for preparing a cement-based repair material is the same as that of the above-mentioned embodiment 2, except that the nano-metal gel admixture used therein is prepared by the following steps:

[0085] (1) 15 parts by weight of vinyl acetate, 10 parts by weight of sodium hydroxide, and 3 parts by weight of water were added to a reactor, and then heated to 50° C. and stirred for 8 minutes. The reactor was then heated to 150° C. and the pressure was set to 1.0 MPa for 4 hours to perform a hydrolysis-polymerization reaction. After completion, the reaction was cooled to room temperature to obtain a liquid phase containing a polymer for standby use.

[0086] (2) 41 parts by weight of the liquid phase containing the polymer was taken and heated to 40° C. for 3 hours to carry out affinity addition reaction. The liquid phase obtained after completion was used for later use.

[0087] (3) Add 0.2 parts by weight of dispersant (methyl cellulose ether) and 1 part by weight of stabilizer (nano-silica) to 40 parts by weight of sodium hydroxide solution with a pH value of 11, and stir magnetically for 8 minutes. Then add 46 parts by weight of the liquid phase of step (2) and high-speed shear at a speed of 1500 r / min for 30 minutes to obtain nano-metal gel.

[0088] Performance test: The infrared test results of this embodiment are as follows Figure 4 In addition, the bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above embodiment 1, and the test results are shown in the following table.

[0089] Bond Strength Flexural strength Elongation at break Cracking index 1.93MPa 9.81MPa 3.49% 63.25%

[0090] Example 6

[0091] 1. A method for preparing a cement-based repair material nano-metal gel admixture, comprising the following steps:

[0092] (1) 28 parts by weight of vinyl acetate, 13 parts by weight of sodium hydroxide, and 10 parts by weight of water were added to a reactor, and then heated to 50° C. and stirred for 10 minutes. The reactor was then heated to 180° C. and the pressure was set to 0.5 MPa for 8 hours to perform a hydrolysis-polymerization reaction. After completion, the reaction was cooled to room temperature to obtain a liquid phase containing a polymer for standby use.

[0093] (2) 61 parts by weight of the liquid phase containing the polymer were taken and heated to 90° C. for 4 hours. The liquid phase obtained after the heating was used for later use.

[0094] (3) Add 0.6 parts by weight of dispersant (polyacrylamide) and 3 parts by weight of stabilizer (sodium silicate) to 55 parts by weight of potassium hydroxide solution with a pH value of 8, and stir magnetically for 12 minutes. Then add 55 parts by weight of the liquid phase of step (2) and high-speed shear at a speed of 5000 r / min for 15 minutes to obtain nanometal gel.

[0095] 2. A method for preparing a cement-based repair material, comprising the following steps:

[0096] (1) Weigh the following components: 45 parts by weight of 42.5 ordinary Portland cement, 60 parts by weight of quartz sand fine aggregate with a fineness between 10 and 100 meshes, 0.25 parts by weight of sodium lignin sulfonate water reducer, 0.6 parts by weight of lithium carbonate powder, 8 parts by weight of ultrafine mineral powder with a fineness of 550 meshes, and 0.3 parts of polyvinyl alcohol fiber with a length of 12 mm. Mix the above components evenly to obtain component A.

[0097] (2) Take 35 parts by weight of the nanometal gel prepared in this example and 10 parts by weight of aluminum acetate powder, mix them with 70 parts by weight of water and stir evenly to obtain component B.

[0098] (3) The component A and the component B are mixed and stirred evenly to obtain a cement-based repair material.

[0099] Performance test: The bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1, and the test results are shown in the following table. It can be seen that when the polymer in step (1) is not pre-polymerized with aluminum acetate, but aluminum acetate is added alone to form component B, since no chemical connection is generated between cement and gel, the performance of the prepared cement-based repair material is significantly reduced.

[0100] Bond Strength Flexural strength Elongation at break Cracking index 2.12MPa 10.34MPa 3.78% 59.41%

[0101] Example 7

[0102] A method for preparing a cement-based repair material comprises the following steps:

[0103] (1) Weigh the following components: 38 parts by weight of 42.5 ordinary Portland cement, 45 parts by weight of river sand fine aggregate with a fineness between 10 and 100 meshes, 0.1 parts by weight of polycarboxylate water reducer, 0.3 parts by weight of sodium sulfate powder, and 5 parts by weight of ultrafine fly ash with a fineness of 600 meshes. Mix the above components evenly to obtain component A.

[0104] (2) The component A and the component B (same as in the above-mentioned embodiment 2) are mixed and stirred evenly to obtain a cement-based repair material.

[0105] Performance test: The bonding strength, flexural strength, elongation at break and cracking index of the cement-based repair material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The test results are shown in the following table.

[0106] Bond Strength Flexural strength Elongation at break Cracking index 2.26MPa 11.15MPa 7.64% 48.55%

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nano-metal gel admixture for cement-based repair materials, characterized in that: The chemical structural formula of the admixture is shown in formula (1):

2. The nano-metal gel admixture for cement-based repair materials according to claim 1, characterized in that: In the formula (1), n=100 to 5000.

3. A method for preparing a nano-metal gel admixture for cement-based repair materials, characterized in that: The steps include: (1) mixing vinyl acetate, alkali solution and water, and subjecting the obtained mixture to a hydrolysis-polymerization reaction under heating and pressure conditions, and obtaining a liquid phase containing a polymer after completion; (2) heating the liquid phase containing the polymer and then keeping it warm, then adding aluminum acetate powder under stirring conditions to carry out affinity addition reaction, and after completion, obtaining a liquid phase containing nano-metal polymer; (3) adding a dispersant and a stabilizer into alkaline water and mixing them evenly, then adding the liquid phase containing the nano-metal polymer and subjecting it to high-speed shearing treatment, and obtaining the nano-metal gel after completion.

4. The method for preparing the nano-metal gel admixture for cement-based repair materials according to claim 3, characterized in that: In step (1), the ratio of vinyl acetate, alkali solution and water is 15-28 parts by weight: 10-13 parts by weight: 3-10 parts; Optionally, in step (1), the alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution; Optionally, in step (1), the heating temperature is 150-180° C., the pressurizing pressure is 0.5-1 MPa, and the reaction time is 4-8 hours.

5. The method for preparing the nano-metal gel admixture for cement-based repair materials according to claim 3, characterized in that: In step (2), the ratio of the liquid phase colloid containing the polymer to the aluminum acetate powder is 41-61 parts by weight: 8-10 parts by weight; Optionally, in step (2), the heating temperature is 40 to 90° C. and the reaction time is 2 to 4 hours.

6. The method for preparing the nano-metal gel admixture for cement-based repair materials according to claim 3, characterized in that: In step (3), the pH of the alkaline water is 8 to 11; Optionally, in step (3), the alkaline water is prepared by mixing alkali solution with water; further optionally, the alkali solution includes at least one of potassium hydroxide solution, sodium hydroxide solution, and saturated calcium hydroxide solution.

7. The method for preparing the nano-metal gel admixture for cement-based repair materials according to claim 3, characterized in that: In step (3), the ratio of the dispersant, the stabilizer, the alkaline water, and the liquid phase containing the nano-metal polymer is 0.2-0.6 parts by weight: 1-3 parts by weight: 40-55 parts by weight: 46-66 parts by weight.

8. The method for preparing the nano-metal gel admixture for cement-based repair materials according to any one of claims 3 to 7, characterized in that: In step (3), the dispersant includes at least one of sodium dodecylbenzene sulfonate, methyl cellulose ether, and polyacrylamide; Optionally, in step (3), the stabilizer includes at least one of nano-silicon dioxide and sodium silicate.

9. Use of the nano-metal gel admixture according to claim 1 or 2, or the nano-metal gel admixture obtained by the preparation method according to any one of claims 3 to 8 in cement-based repair materials, characterized in that: The raw material composition of the repair material includes component A and component B, wherein: The component A comprises 38-45 parts by weight of silicate cement, 45-60 parts by weight of quartz sand, 0.1-0.25 parts by weight of water reducing agent, 0.3-0.6 parts by weight of early strength agent, 5-8 parts by weight of superfine powder, and 0.1-0.3 parts by weight of fiber; The B component comprises the cement-based repair material nano-metal gel admixture according to claim 1 or 2, or 20 to 35 parts by weight of the cement-based repair material nano-metal gel admixture obtained by the preparation method according to any one of claims 3 to 8, and 50 to 70 parts by weight of water.

10. The use according to claim 9, characterized in that: The water reducer includes at least one of a polycarboxylate water reducer, a naphthalene water reducer, and a lignin sulfonate water reducer; Optionally, the early strength agent includes at least one of sodium sulfate, lithium carbonate and sodium silicate; Optionally, the ultrafine powder includes at least one of fine fly ash, ultrafine mineral powder, and ultrafine composite mineral admixture; Optionally, the fiber includes at least one of carbon fiber, polypropylene fiber, polyvinyl alcohol fiber, and polyacrylonitrile fiber; Optionally, the length of the fiber is 3 to 12 mm.

Citation Information

Patent Citations

  • Preparation method of supermolecule gel-based composite phase change material

    CN104893673A

  • In-situ complexation ultraviolet absorption high-weather-resistance protective coating and preparation method thereof

    CN118725167A

  • High-temperature self-crosslinking-based flame-retardant Anti-dripping copolyester, and preparation method therefor and application thereof

    US20230235116A1

  • Latex / sol or GEL systems

    WO1990008798A1

  • Rapid set cement foam and the method for preparing the same

    WO2008130107A1